2015
DOI: 10.1016/j.rmed.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eosinophilia in hospitalized patients with asthma exacerbation

Abstract: Our pilot study showed that 40% of patients hospitalized for asthma exacerbation had eosinophilia. The clinical meaning of this biomarker in the emergency department/inpatient setting requires further study in much larger samples with long-term follow-up; such studies appear feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
1
17
1
Order By: Relevance
“…Nevertheless, we found a significant inverse association between eosinophil count and risk of admission. This finding differs from those of the pilot study by Hasegawa et al [44], who found that, of 80 patients hospitalized for asthma exacerbation, 32 patients (40%) had blood eosinophilia (300/mm 3 ). However, the study was limited by the inclusion of patients with severe acute asthma in the analytic cohort population, which may suggest that their study population was in poorer health than the overall population of patients hospitalized for asthma exacerbation.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, we found a significant inverse association between eosinophil count and risk of admission. This finding differs from those of the pilot study by Hasegawa et al [44], who found that, of 80 patients hospitalized for asthma exacerbation, 32 patients (40%) had blood eosinophilia (300/mm 3 ). However, the study was limited by the inclusion of patients with severe acute asthma in the analytic cohort population, which may suggest that their study population was in poorer health than the overall population of patients hospitalized for asthma exacerbation.…”
Section: Discussioncontrasting
confidence: 99%
“…The primary outcome was prevalence of blood eosinophilia. Based on the literature, eosinophilia was defined as an absolute eosinophil count ≥300 cells/μL in peripheral blood on the first‐measured cell counts with differentials during the in‐hospital course (including pre‐hospitalization emergency department/clinic visit). Additionally, based on the other COPD studies, we also used an alternative cut‐off of ≥2% of total white cell count in peripheral blood.…”
Section: Characteristics and Outcomes Of Patients Hospitalized For Acmentioning
confidence: 99%
“…A small pilot study from Japan (n = 47) did not find any differences among patients hospitalized for asthma exacerbation in initial vital signs, requirement for ventilatory support or disposition between those with eosinophils ≥0.3 × 10 9 /L compared with those with eosinophils <0.3 × 10 9 /L, but the study was underpowered. 30 A study of 1316 patients admitted with non-life threatening exacerbations reported that an eosinophil count of ≥0.4 × 10 9 cells/L was associated with a reduction in late Step 5 readmission risk of 41% and a decrease in frequent late readmission of 63%. 31 An important limitation in many of these studies is the arbitrary selection of eosinophil count thresholds which were presumably extrapolated from studies evaluating blood eosinophil count as a pharmacodynamic biomarker of response to biologics, for example, ≥0.150 or 0.300 × 10 9 /L for mepolizumab, ≥0.300 × 10 9 /L for benralizumab and ≥0.400 × 10 9 /L for reslizumab.…”
Section: Discussionmentioning
confidence: 99%